THE EFFECTIVENESS OF FLIPPED CLASSROOM MODEL TOWARDS STUDENTS LISTENING COMPREHENSION IN THE TENTH GRADE OF SMAN 1 BADEGAN - Ayu Indah Pambayu, Risma; Siti Asiyah; Niken Reti Indriastuti (Pedagogic Research-Applied Literacy Journal, 2024)
The goal of this study is to determine the effectiveness of the flipped classroom model in listening comprehension in the tenth grade students of SMAN 1 Badegan, Ponorogo foe the academic year 2023/2024. Two groups (control and experimental) were employed in this study, which used a true-experimental post-test only design. The subject of this study are tenth grade. 67 students were selected using probability simple random sampling technique, which 33 students in the experimental group (X8) and 34 students in control group (X2). A listening test was used to gather data. the findings showed that flipped classroom model is effective towards students' listening comprehension. This is supported by the fact that the average score of students in the experimental group was higher than the average of the students in the control group (87.82>64.41). In addition, the results of the hypothesis test show a significance (2-tailed) is 0.000. Since, significance (2-tailed) = 0.000 < 0.05, the alternative hypothesis (Ha) is accepted and the null hypothesi (Ho) is rejected. From the results of the study, it was concluded that the flipped classroom model is effective in improving students' listening comprehension.